2014
DOI: 10.1088/1367-2630/16/1/013025
|View full text |Cite
|
Sign up to set email alerts
|

Interference of macroscopic beams on a beam splitter: phase uncertainty converted into photon-number uncertainty

Abstract: Squeezed-vacuum twin beams, commonly generated through parametric downconversion, are known to have perfect photon-number correlations. According to the Heisenberg principle, this is accompanied by a huge uncertainty in their relative phase. By overlapping bright twin beams on a beam splitter, we convert phase fluctuations into photon-number fluctuations and observe this uncertainty as a typical 'U-shape' of the output photon-number distribution. This effect, although reported for atomic ensembles and giving h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In contrast to the TMSVS, the pair coherent states exhibit sub-Poissonian photon statistics in each mode. Recently, Spasibko et al [25] experimentally examined the interference effects and photon-number fluctuations from TMSVS whose twin beams fall on opposite sides of a beam splitter.…”
Section: Beam Splitting and Multiphoton Interferencementioning
confidence: 99%
“…In contrast to the TMSVS, the pair coherent states exhibit sub-Poissonian photon statistics in each mode. Recently, Spasibko et al [25] experimentally examined the interference effects and photon-number fluctuations from TMSVS whose twin beams fall on opposite sides of a beam splitter.…”
Section: Beam Splitting and Multiphoton Interferencementioning
confidence: 99%
“…We found that condensate depletion reduces the odd/even discrete structure of the typical U-shaped particle distribution that arise when measuring the different numbers of particles populating both modes. Such an odd/ even fluctuation reduction is very similar to that caused by particle losses [5,6,8]. Condensate depletion also renders the standard deviation of the interfering mBECs to be smaller, as compared with the one given by the ideal BECs interference of bosonic atoms.…”
Section: Introductionmentioning
confidence: 76%
“…For k a 1 4 F = ( ) (Green dots) the probability of the different population imbalances match the ideal bosonic behavior (gray shaded histogram), whereas for k a 1 1 F = ( ) the even/odd particle fluctuations almost vanishes. Particle losses and/or the absence of single-particle resolution in the experiments also render even/odd fluctuations vanishes [5,6]. Nevertheless, the U-shape of the probability distribution, considered in the literature as an indicator for possible entanglement-enhanced phase resolution [4][5][6][7][8], is preserved.…”
Section: Populations Imbalancementioning
confidence: 97%
See 2 more Smart Citations